High Moisture Stability for Enhanced Quality Perovskite Solar Cells Induced by Front and Back Layer Synergistic Passivation of Perovskite. Issue 10 (5th August 2022) - Gong, Xiaoli; Li, Haimin; Liu, Xingchong; Wang, Hanyu; Ni, Yafei; Lei, Yue; Zhou, Ruonan; Zou, Wenjing; Tang, Yanling; Liu, Shuqian
Abstract : Moisture stability is one of the key factors that hinders the commercialization of perovskite solar cells (PSCs). Herein, a new method of front and back layer synergistic passivation of perovskite is investigated. On the front layer, porous PbI2 nanostructures are induced by N ‐ tert ‐butyl‐2‐benzothiazolesulfenamide (TBBS), which is added into PbI2 precursor solution and thermally decomposed to tert ‐butylamine (TBA) and 2‐mercaptobenzothiazole (2‐MBT) during annealing process. TBA volatilization leaves voids to induce porous PbI2, promoting diffusion of organic salts, facilitating crystallization of perovskite. Thickness of perovskite with TBBS doping increases from 527.7 to 561.2 nm, and the champion power conversion efficiency (PCE) increases from 19.71% to 20.97%. On the back layer, hydrophobic hole transport material PTAA is introduced onto perovskite surface to fill cation vacancies. Eventually, the highest efficiency of 22.35% with outstanding moisture stability is achieved after front and back layer synergistic passivation, which can maintain 71.14% of its initial efficiency after 7 days under high relative humidity (RH = 65 ± 2%) in ambient conditions without any encapsulation, while the control one can only remain 12.38%. Abstract : N ‐ tert ‐butyl‐2‐benzothiazolesulfenamide (TBBS) is added to the PbI2 precursor solution and thermally decomposes to yield volatile tert ‐butylamine, which volatilizes during annealing to induce porous PbI2 . On front layer of perovskite, S‐H combines with uncoordinated Pb 2+ and branches of hydrophobic PTAA fill MA + vacancies on back layer to achieve synergistic passivation, enhancing the stability of device.